ELEMENTAL ESTIMATION OF OPERATORS’ PSYCHOPHYSIOLOGICAL STATE IN MAN-MACHINE CONTROLE SYSTEMS - K A Pupkov (RUDN Journal of Engineering Research, 2015)
A problems of operators’ psychophysiological parameters estimation in man-machine systems is considered. To estimate the psychophysiological parameters it is proposed to use a pure time delay of operator and motor activity delay. It is show that integral delay may be effective integral estimation for man - operator state and its psychophysiological parameters.